2013
DOI: 10.1101/gr.150482.112
|View full text |Cite
|
Sign up to set email alerts
|

DNase-seq predicts regions of rotational nucleosome stability across diverse human cell types

Abstract: DNase-seq is primarily used to identify nucleosome-depleted DNase I hypersensitive (DHS) sites genome-wide that correspond to active regulatory elements. However,~40 yr ago it was demonstrated that DNase I also digests with a~10-bp periodicity around nucleosomes matching the exposure of the DNA minor groove as it wraps around histones. Here, we use DNase-seq data from 49 samples representing diverse cell types to reveal this digestion pattern at individual loci and predict genomic locations where nucleosome ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 41 publications
3
26
0
Order By: Relevance
“…This is most likely due to dynamic nucleosome wrapping and unwrapping (DNA breathing) (Li and Widom 2004;Li et al 2005). Overlaid on this quadratic shape, we also observe a signature oscillatory cleavage pattern, which has been previously wellestablished (Noll 1974;Boyle et al 2008;Winter et al 2013). Since DNase I binds within the minor groove, it can more easily nick nucleosomal DNA when the minor groove is exposed.…”
Section: Dnase Cleavage Shows a Distinctive Oscillatory Profile Alongmentioning
confidence: 71%
See 4 more Smart Citations
“…This is most likely due to dynamic nucleosome wrapping and unwrapping (DNA breathing) (Li and Widom 2004;Li et al 2005). Overlaid on this quadratic shape, we also observe a signature oscillatory cleavage pattern, which has been previously wellestablished (Noll 1974;Boyle et al 2008;Winter et al 2013). Since DNase I binds within the minor groove, it can more easily nick nucleosomal DNA when the minor groove is exposed.…”
Section: Dnase Cleavage Shows a Distinctive Oscillatory Profile Alongmentioning
confidence: 71%
“…This indicates that if a DNase-based nucleosome center does not coincide with a reference nucleosome center, it is far more likely to be a multiple of 10.3 bp away from it. Many have reported that nucleosomes exhibit this translational positioning offset property, in which a nucleosome is likely to position itself at "rotationally in-phase" positions that are multiples of 10.3 bp away from each other (Albert et al 2007;Brogaard et al 2012;Gaffney et al 2012;Winter et al 2013). We believe that our DNase-seqbased approach identifies genuine nucleosome centers, and where the map does not perfectly coincide with the reference, the differences appear to represent translational offsets with respect to reference nucleosome centers.…”
Section: Distinctive Dnase Cleavage Profile Allows Nucleosome Positiomentioning
confidence: 98%
See 3 more Smart Citations